We Have Enough Neurotypical Thinkers Already: Why Accommodating and Developing a Neurodiverse Workforce is the Right Strategic Approach to Navigating the Fourth Industrial Revolution - Fellows, Ian (GILE Journal of Skills Development, 2025)
With the development of advanced technologies such as Large Language Models (LLMs), 3D printing, the Internet of Things, blockchain technologies, advanced robotics, material ecology and driverless vehicles, the requirements from the workforce of the future will be significantly different from the workforce we have today. This paper explores the potential for organisations to proactively manage this problem by adopting an approach that accommodates a neurodiverse workforce more effectively. Placing the fourth industrial revolution and volatile, uncertain, complex, and ambiguous (VUCA) economy in a broad historical context informs the discussion on why and how this accommodation may be effectively achieved. This paper adds to the knowledge by identifying positive correlations between the emerging labour market and the underleveraged potential of neurodiverse employees. In addition to its constructive recommendations to employers and educators, this paper offers positive guidance to young neurodiverse people entering the labour market.